2016
DOI: 10.1007/s12040-016-0695-9
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic observations from southwestern terminus of Palghat Gap, south India and their tectonic implications

Abstract: The region around Wadakkancheri, Trichur District, Kerala is known for microseismic activity, since 1989. Studies, subsequent to 2nd December 1994 (M=4.3) earthquake, identified a south dipping active fault (Desamangalam Fault) that may have influenced the course of Bharathapuzha River. The ongoing seismicity is concentrated on southeast of Wadakkancheri and the present study concentrated further south of Desamangalam Fault. The present study identifies the northwestern continuity of NW-SE trending Periyar lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Some of the fault related geological studies in Peninsular India (Wadakkancheri, Periyar and Thenmala faults) identified that the region is responding to compressive tectonic regime [22,25,26]. The slickensides from these faults indicate the recent movements are consistent with the present tectonic stress regime.…”
Section: Vithe Regional Stress Conditionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Some of the fault related geological studies in Peninsular India (Wadakkancheri, Periyar and Thenmala faults) identified that the region is responding to compressive tectonic regime [22,25,26]. The slickensides from these faults indicate the recent movements are consistent with the present tectonic stress regime.…”
Section: Vithe Regional Stress Conditionsmentioning
confidence: 98%
“…Drainage system of the area is also controlled by the NW-SE trending lineaments corresponding to Periyar lineament that enters into Palghat-Cauvery shear zone. Singh et al, [25] identified that the continuity of this fault as segmented lineaments in the northwestern end and have induced drainage anomalies in the area. Their studies identified subtle landform modifications induced by ongoing tectonic adjustments in the area.…”
Section: Ivobservation On Neotectonism In Palghat-cauvey Shear Zonementioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study of the morphometric parameters with seismic activity showed that the tectonic tilt, high deformation activity produces folded structures which are responsible for earthquakes and seismotectonic activity in the Jia Bhareli river catchment in the eastern Himalaya (Duarah and Phukan 2011). A study of the geomorphic observations and their tectonic implications reveals that the anomalies in the morphometric parameters correspond to lineaments, faults and micro seismic activities of the Palghat gap in south India (Singh et al 2016). Bhattacharya et al (2013) investigated the morphometric evidences of seismic activity in the Wagad and Gedi faults, Eastern Kachchh, Gujarat by analysing various morphometric parameters which reveal that the asymmetric nature of basin and stream migration suggests lateral displacements of faults, tectonic instability and seismic activity.…”
Section: Introductionmentioning
confidence: 99%
“…It is formed due to the displacements of structural features and deformation of rock masses (Kuk et al 2000). The analysis of drainage morphometric parameters and identification of geomorphic anomaly are key to seismotectonic studies (John and Rajendran 2008;Singh et al 2016). Silva et al (2003) studied the geomorphic indices for the assessment of tectonic and seismic activities in Spain which showed that the variation of geomorphic anomalies such as upliftment, discrete surface rupture, etc., determine the active tectonic process and seismic activity.…”
Section: Introductionmentioning
confidence: 99%